High yield growth and doping of black phosphorus with tunable electronic properties. (June 2020) - Liu, Mingqiang; Feng, Simin; Hou, Yi; Zhao, Shilong; Tang, Lei; Liu, Jiaman; Wang, Feng; Liu, Bilu
Graphical abstract: A facile approach using SDT method under uniform temperature have been applied to synthesize high yield, high purity and high-quality BP crystals. In addition, uniform and controllable doping of various elements are also achieved with the same method. Abstract: Black phosphorus (BP) has recently attracted significant interest due to its unique electronic and optical properties. Doping is an effective strategy to tune a material's electronic properties, however, the direct and controllable growth of BP with a high yield and its doping remain a great challenge. Here we report an efficient short-distance transport (SDT) growth approach and achieve the controlled growth of high quality BP with the highest yield so far, where 98% of the red phosphorus is converted to BP. The doping of BP by As, Sb, Bi, Se and Te are also achieved by this SDT growth approach. Spectroscopic results show that doping systematically changes BP's electronic structures including band gap, work function, and energy band position. As a result, we have found that the air-stability of doped BP samples (Sb and Te-doped BP) improves compared with pristine BP, due to the downshift of the conduction band minimum with doping. This work reports a new method to grow BP and doped BP with tunable electronic structures and improved stability, and should extend the uses of these class of materials in various areas.